Health status assessment of related kidney donors in the late postoperative period - Nykonenko, A. O.; Nykonenko, O. S.; Buga, D. A.; Rusanov, I. V.; Vildanov, S.R.; Никоненко, Андрій Олександрович; Никоненко, Олександр Семенович; Вільданов, Сергій Ренатович (My University, 2020)
To analyze the health status of living kidney donors based on the degree of restoration of the kidney function and the general physical status of the donor. Methods. 37 related kidney donors underwent nephrectomy between 2014 and 2017. The average age was 48.3±9.7 (м±σ) years, with 19 men (51%) and 18 (49%) women. In the late postoperative period (1,9±1,1 years (м±σ)), the levels of proteinuria, and glomerular filtration rate (GFR) were studied. The life quality of kidney donors was assessed using the Medical Outcomes Study-Short Form-36 questionnaire. Results. The average GFR before the operation was 78,9±24,5 ml/min per 1.73 m2 , and fell to 49,8±11,2 ml/min per 1.73 m2 on the 2nd day after the operation. Upon discharge (15,2±7,0 day), average GFR increased to 53,4±8,0 ml/min per 1.73 m2 , and almost reached pre-operation levels 1,9±1,1 years after the operation. This suggests that a single normally-functioning kidney is capable of taking on the load from the missing kidney. Furthermore, our study showed that, in the late postoperative period, there was no statistically significant difference in either GFR or quality of life between the donors of different age groups (p>0.05). Our research showed that if adequate protocols are used for living donor selection, donor-recipient kidney transplantation is not only an effective method for treating terminal stage of chronic end stage of renal disease, but is also safe for health and the subsequent renal function of the donor. Conclusions. In living donors, a gradual restoration of renal function is observed, according to GFR, at discharge (day 15.2±7.0) and in the late postoperative period (1.9±1.1 years), almost reaching the preoperative level. The physical and psychological health components of donors of different age groups were comparable. изучить состояние здоровья живых доноров почки на основании степени восстановления функции почки и общего физического статуса донора. Материал и методы. 37 родственных доноров почек перенесли нефрэктомию в период с 2014 по 2017 год. средний возраст составил 48,3±9,7 года (м±σ), мужчин было 19 (51%), женщин – 18 (49%). в позднем послеоперационном периоде (1,9±1,1 года (м±σ)) изучали уровни протеинурии и скорости клубочковой фильтрации (скФ). качество жизни доноров почек оценивали с помощью опросника Medical Outcomes Study-Short Form-36. Результаты. средняя скФ до операции составила 78,9±24,5 мл/мин на 1,73 м2 и снизилась до 49,8±11,2 мл/мин на 1,73 м2 на 2-е сутки после операции. при выписке (15,2±7,0 LYZ) средняя скФ увеличивалась до 53,4±8,0 мл/мин на 1,73 м2 и практически достигла предоперационного уровня через 1,9±1,1 года. отмечено повышение креатинина и увеличение протеинурии в ранние сроки с нормализацией этих показателей в отдаленные сроки. Это свидетельствует о том, что единственная почка с нормальной функцией способна компенсировать отсутствие контралатеральной. кроме того, наше исследование показало, что в позднем послеоперационном периоде не было статистически значимой разницы ни по скФ, ни по качеству жизни между донорами разных возрастных групп. таким образом, при адекватной селекции пары донор-реципиент на основе комплексного обследования, трансплантация почки является не только эффективным методом лечения терминальной стадии хронической почечной недостаточности, но и безопасна для здоровья и дальнейшей почечной функции донора. Заключение. у прижизненных доноров отмечается постепенное восстановление почечной функции, согласно скФ, при выписке (день 15,2±7,0) и в позднем послеоперационном периоде (1,9±1,1 года) практически до предоперационного уровня. Физический и психологический компоненты здоровья доноров разных возрастных групп были сопоставимы.
Keywords: transplantation; living kidney donor; donor nephrectomy; postoperative period; renal failure; трансплантація; прижизненный донор почки; донорская нефрэктомия; послеоперационный период; почечная недостаточность